SmDXS5, acting as a molecular valve, plays a key regulatory role in the primary and secondary metabolism of tanshinones in Salvia miltiorrhiza - Zhang, Da-chuan; Luo, Ling-long; Wang, Zhi-rong; Xu, Wen-juan; Li, Jun-ling; Tan, Shu-ting; Wu, Jia-hui; Li, Yan; Zhang, Chi; Liang, Chen; Wang, Xue-yong (Frontiers in Plant Science, 2022)
Red sage, the dry root and rhizome of the herbaceous plant Salvia miltiorrhiza Bunge, is widely used for treating various diseases. The low content of tanshinones (terpenoids) has always restricted development of the S. miltiorrhiza industry. Here, we found that SmDXS5, a rate-limiting enzyme-coding gene located at the intersection of primary and secondary metabolism, can effectively change the transcription level and secondary metabolome profile of hairy roots of S. miltiorrhiza, and significantly increase the content of tanshinones. Agrobacterium rhizogenes was used to infuse S. miltiorrhiza explants, and hairy roots of S. miltiorrhiza expressing the SmDXS5 gene were obtained successfully. We identified 39 differentially accumulated metabolites (DAMs) by metabolomics based on ultra-high performance liquid chromatography quadrupole exactive mass spectrometry and multivariate statistics. These DAMs might be key metabolites of SmDXS5 gene regulation. RNA sequencing was used to compare gene expression between the hairy roots of the SmDXS5 overexpressing group and the blank control (BC) group. Compared with the BC group, 18,646 differentially expressed genes were obtained: 8994 were upregulated and 9,652 downregulated. The combined transcriptome and metabolome analyses revealed that the mevalonate and methylerythritol phosphate pathways and synthase gene expression levels in the SmDXS5 overexpressing group were upregulated significantly, and the accumulation of tanshinone components was increased significantly, which promoted the process of glycolysis and promoted the transformation of carbohydrates to secondary metabolism. Moreover, the expression of SmPAL, the first rate-limiting enzyme gene of the phenylpropane pathway, decreased, reducing the accumulation of phenolic acid, another secondary metabolite. Therefore, SmDXS5 can be defined as a ‘valve’ gene, mainly responsible for regulating the distribution of primary and secondary metabolic flow of tanshinones in S. miltiorrhiza, and for other secondary metabolic pathways. The discovery of SmDXS5 and its molecular valve function in regulating primary and secondary metabolism will provide a basis for the industrial production of tanshinone components, and cultivation of high quality S. miltiorrhiza.